2010
DOI: 10.4314/thrb.v11i4.50143
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and severity of cervical squamous intraepithelial lesion in a tertiary hospital in northern Tanzania

Abstract: Cervical cancer is the second most common cancer in women worldwide and the leading cause of cancer deaths in Tanzanian women. Prevention of cervical cancer relies on the detection and treatment of Squamous Intraepithelial Lesion (SIL), a premalignant disease stage. Worldwide there are overwhelming reports associating SIL and HIV infection, however in Tanzania such reports are limited. A cross-sectional hospital-based descriptive study was conducted to determine the prevalence and severity of SIL in 234 HIV se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
16
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(22 citation statements)
references
References 13 publications
4
16
2
Order By: Relevance
“…Having multiple sexual partners increases the chance of acquiring. Studies that have been conducted in both rural and urban areas show that significant association between having multiple sexual partners and cervical cancer [11]. A study in Morocco shows that promiscuity and polygamist which is related to multiple sexual partners increases the risk of cervical cancer [11].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Having multiple sexual partners increases the chance of acquiring. Studies that have been conducted in both rural and urban areas show that significant association between having multiple sexual partners and cervical cancer [11]. A study in Morocco shows that promiscuity and polygamist which is related to multiple sexual partners increases the risk of cervical cancer [11].…”
Section: Discussionmentioning
confidence: 99%
“…Studies that have been conducted in both rural and urban areas show that significant association between having multiple sexual partners and cervical cancer [11]. A study in Morocco shows that promiscuity and polygamist which is related to multiple sexual partners increases the risk of cervical cancer [11]. The finding of this study reveals that multiple sexual partners are significantly associated with cervical cancer as compared to those women who have no exposure of multiple sexual partners (AOR=40; 95% CI: 22.44,70.204) and having history of STI exposure and being HIV positive became significant with the outcome variable of the study as compared to those women who have no history of STI exposure and HIV negative (AOR=8.3 :95%CI: 5.639,12.405) and (AOR=9:95% CI: 9:4.537,17.985) respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Another possibility, although not investigated in this study, could be the fact that a large proportion of the participants, due to their single marital status, may be involved in multiple sexual partner relationships. A Tanzanian study found that single marital status and number of lifetime sex partners were risk factors, significantly associated with SIL (Obure et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…But Obure et al (2009) reported no influence of parity on the risk of abnormal Pap smear among Tanzanian HIV positive women. In their account, only marital status and multiple sexual partners were significantly associated with an increased risk of cervical cytological abnormalities among the women.…”
Section: Discussionmentioning
confidence: 95%